KARAKTERISASI PERTUMBUHAN DAN HASIL TANAMAN BUNGA TELANG BIRU DAN BUNGA TELANG PUTIH - Ummu Kalsum; Budiman Budiman (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2023)
The butterfly pea plant is one of the plants that is an alternative to natural dyes and contains compounds that are efficacious for human health. Telang plants cultivated in Indonesia have various flower crown colors, namely blue, white, and purple. The diversity of crown colors is suspected that each type has distinctive yield growth characteristics, so it is important to conduct research on certain characteristics of various colors of butterfly pea flower plants. The purpose of this study was to examine the growth and yield of blue butterfly pea flowers and white butterfly pea flowers. The study used 1 factor or non-factorial experimental design, namely the treatment of the type of butterfly pea flower (white butterfly pea flower and blue butterfly pea flower). The microclimate of the butterfly pea plannting site is measured at air temperature and humidity. Observational variables in this experiment during vegetative growt and harvest. Observational variabels of vegetative growth include plant length and number of leaves, while at harvest are length and weight of plant canopy, roots and overall plant and number of flowers. The data obtained were analyzed using a t-test α=0.05. The results showed that white butterfly pea plants have higher vegetative growth (length and number of leaves) and the harvest caracters (such as canopy, roots, whole plant, and number of flowers) than blue butterfly pea plants